Iridium complex loaded polypyrrole nanoparticles for NIR laser induced photothermal effect and generation of singlet oxygen. Issue 19 (5th February 2016) - Xue, Fengfeng; Shi, Min; Yan, Yuping; Yang, Hong; Zhou, Zhiguo; Yang, Shiping
Abstract : Iridium complex loaded polypyrrole nanoparticles have been prepared and show a NIR laser induced photothermal effect and the generation of singlet oxygen. Abstract : Iridium complex loaded polypyrrole nanoparticles (Ir-PPy NPs) have been prepared through the polymerization of pyrrole by Fe 3+ in the presence of polyvinyl alcohol (PVA) and iridium complex. The Ir-PPy NPs exhibited a photothermal effect and the generation of singlet oxygen. In the Ir-PPy NPs, PPy could convert light energy to heat with a photothermal conversion efficiency of ∼35.5% when irradiated by a 730 nm continuous wave (CW) laser, and the iridium complex could generate singlet oxygen when irradiated by a 730 nm CW laser, as confirmed by monitoring the consumption of DPBF at 410 nm.